Absorption and Sinking Speed of Artocarpus Stems Rope (Artocarpus sp.) and Carex Grass Rope (Carex sp.) in Freshwater and Seawater - Amraini Fitri; Nofrizal Nofrizal; Romie Jhonnerie; Fauzan Ramadhan (Fakultas Perikanan dan Kelautan Universitas Riau, 2022)
Artocarpus stems (Artocarpus sp.) and Carex grass (Carex sp.) have not been applied to fishing gear materials. The fibers produced made into a rope, where this rope is used to absorption and sinking speed test in fresh water and sea water.The absorption of Artocarpus stems rope was 320.30% and 282,60% in fresh water and sea water. Meanwhile for sinking speed have a 5,78 cm/s and 5,08 cm/s for fresh water and sea water. For the Carex grass rope, the absorption in fresh water and sea water was 287,67% and 218,02%. Sinking speed value 2,97 cm/s and 2,67 cm/s for fresh water and sea water. The value of absorption and sinking speed in fresh water is higher than in sea water for both types of rope